The Impact of Climate Change (some Element) on Field Crops in Baghdad Province - Al–Jubouri, Hind Fadhil Ibrahim (Al-Adab Journal, 2021)
The study aimed to analyze the impact of climate change, which included elements actual brightness, degrees of normal temperature and the maximum and minimum, wind speed, relative humidity, rainfall, evaporation in the change of field crops and its implications in the province of Misaan, and the impact of those changes in the area and the yields and production of selected agricultural crops They wheat, barley, rice, maize has been relying in this study on the data of Two weather stations are (Misaan ,AL hay) for the period (1960-2014), it has been the general trend and the rate of change coefficient the annual rate of change during the duration of the study for an average of different climatic elements, showing the direction of the solar brightness in all stations downward direction different temperatures upward ranged Other elements between the rise and fall according to the stations on the impact of this rise and fall with the climate elements on an area and yields and production of field crops, which include each of wheat, barley, rice, maize.